The Influence Of Work Stress And Leadership Style On Employee Turnover Intention At Josh's Car Wash & Auto Detailing Ciganjur Lama Branch - Putri, Pebi Nabila; Sutrisna, Arga; Oktaviani, Nita Fauziah (Journal of Management, Economic, and Accounting, 2025)
This research aims to determine the simultaneous and partial effects of work stress and leadership style on employee turnover intention at Josh's Wash & Auto Detailing Ciganjur Lama Branch. The method used in this research is quantitative with a survey approach. With a sample of 40 people as respondents from the Josh's Wash & Auto Detailing Ciganjur Lama Branch based on the known population data of 40. The data used is primary data. The analytical tool used in this research is multiple linear regression using SPSS version 25 software. Simultaneously, work stress and leadership style have a significant effect on employee turnover intention. Partially, the work stress variable has a significant effect on employee turnover intention, as well as the leadership style variable, which also significantly affects employee turnover intention.